Modeling the potential influence of subsurface tile drainage systems on downstream flooding in a midwestern agricultural watershed - White, Heather (Kansas State University, 2023)
Subsurface drainage systems are common in agricultural regions of the Midwestern United States. Drainage systems remove excess water from the surface and soil profile of agricultural fields, allowing crop production in previously unsuitable locations. However, drainage systems impact watershed hydrology and could, depending on site-specific factors, influence flooding events. Therefore, this study determines whether subsurface tile drainage systems influence daily downstream flooding from a midwestern, agricultural watershed: Skunk Creek watershed. In this study, the Soil and Water Assessment Tool (SWAT) model is used to simulate the hydrologic processes of Skunk Creek Watershed for a period of 18 years (2004-2021). The model is calibrated and validated using observed daily streamflow data with the SWAT Calibration and Uncertainty Program (SWAT-CUP) software, as well as through the manual addition of missed precipitation data. The statistical parameters Nash Sutcliffe Efficiency (NSE), Percent Bias (PBIAS), and RMSE-Observations Standard Deviation Ratio (RSR) are used to evaluate the fit and accuracy of the model, with the daily NSE ranging from 0.595 to 0.790, PBIAS ranging from -2.588 to 25.808, and RSR ranging from 0.636 to 0.458. The calibrated and validated model is used as the baseline scenario, and five tile drainage scenarios—ranging from 15% to 75% tile-drained agricultural land—are individually incorporated into the model. It was observed that as the area of tile-drained land increases, the depth of tile flow contributing to daily streamflow increases. Additionally, surface runoff, groundwater flow, deep aquifer recharge, and percolation decrease, whereas lateral soil flow, tile flow, evapotranspiration, and water yield increase. A comparison of tile drainage scenarios suggests that increasing the amount of tile-drained agricultural land decreases the total number of flood events (flood days). However, the impact of tile drainage systems on downstream flood peak flows was found to vary by event. Large precipitation events (greater than 300 mm/day) were found to initiate flood days with similar peak flows across all scenarios. Future studies can replicate the approach with a sub-daily time-step for simulating hourly flood events with various tile drainage scenarios.
Keywords: Streamflow; SWAT; Tile drainage; Midwest; Watershed hydrology